PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Studi Empiris Pada Pegawai Komisi Penanggulangan AIDS (KPA) Provinsi Jawa Tengah) - Shinta Ratnawati, 12.5202.0206; Soliha, Euis (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to test the servant leadership, compensation effect on motivation, leadership and compensation does serve effect on organizational commitment, whether the motivation effect on organizational commitment. The population in this study were employees of AIDS Commission in 35 districts and cities in Central Java, amounting to 140 employees and also AIDS Commission, Central Java Province, amounting to 12 people. So the total population used in this study were 152 employees. The sampling technique used is by using census sampling the entire population sampled. The results of this study indicate that servant leadership is a positive effect on employee motivation AIDS Commission in Central Java, the compensation has no effect on employee motivation, servant leadership has positive influence on organizational commitment on employee AIDS Commision in Central Java, motivation positive effect on organizational commitment, motivation proved to mediate the effect of servant leadership on organizational commitment. Keywords: servant leadership, compensation, motivation, and organizational commitment